Indígenas, jesuítas e colonos: o Guarani no alto Vale do Rio dos Sinos e a ação inaciana entre os Carijó (séculos XVI e XVII) - Nunes, Jefferson Aldemir (Universidade do Vale do Rio dos Sinos, 2019)
This paper has as theme the Guarani settlement in the upper Rio do Sinos valley, taking as a problem the development of settlements in the Basin and its relationship with the Jesuit missionary expansion front. Its objectives the study of the material native culture developed by the Guarani in the upper Rio do Sinos valley, the description of the Jesuit documents about their relationship with the native Carijó Indians of the South-Brazilian coast, their way of life in the XVI and first half of the XVII century, and the construction of a model for the settlement of the Guarani in the upper Rio do Sinos valley, joining archaeological and historical sources. The methodology involved, for the archaeological part, the historical-culturalism of Betty Meggers and Clifford Evans (1970) and, for the documents, elements of Melià’s Ethno-history (1987), Content Analysis by Laurence Bardin (2016) and direct analogy. The results point to the development of a settlement pattern characteristic of these populations in the Sinos valley, the impact that the arrival of Europeans has had on the Guarani way of life, and how the use of distinct sources can help build a more plural history of the indigenous peoples in these first contacts.
Keywords: Povoamento Guarani; Rio dos Sinos; Jesuítas; Expansão colonial; Guarani settlement; Rio dos Sinos valley; Jesuits; Colonial expansion